EXPLORING EFL LEARNERS’ AGENCY IN ONLINE ENGLISH LANGUAGE TEACHING DURING THE COVID 19 PANDEMIC - Tedi Rohadi; Listiana Ikawati; Muhsiyana Nurul Aisyiyah (English Review: Journal of English Education, 2023)
This qualitative descriptive study intends to investigate how student agency skills were affected by online EFL instruction during the COVID-19 epidemic, as well as how it would have affected future learning and teaching. The study focuses on pre-service student teachers in Indonesia, aiming to equip them with the necessary skills for academic success and the modern job market. The results show that learners' agency was essential to their adjustment to the online learning environment, especially when taking into account elements like choice, fairness, participation, interest, motivation, self-efficacy, teacher support, and peer support. Moreover, the study highlights the importance of fostering student agency in EFL teaching and learning activities, which not only provide content-based learning but also create collaborative language learning environments that empower learners to utilize a variety of online resources and tools. Overall, this study provides insights into the effective implementation of online language education during unprecedented times while emphasizing the importance of student agency for successful EFL learning and teaching.